Multilateral Debt Relief Initiative and Exogenous Shocks Facility : Proposed Decisions. (Policy Papers; Policy Paper ;, 2005)
This paper puts forward a package of proposed decisions to implement the Multilateral Debt Relief Initiative ('MDRI') and establish the Exogenous Shocks Facility within the PRGF Trust; it also provides a Commentary on key aspects of the decisions. The proposed decisions generally reflect the overall structure and modalities that have been identified by the staff and endorsed by Executive Directors in the several meetings held to date concerning the G-8 debt relief proposal/MDRI and ESF.